2016
DOI: 10.1111/pde.12896
|View full text |Cite
|
Sign up to set email alerts
|

Agminated Fibroblastic Conective Tissue Nevus: A New Clinical Presentation

Abstract: Connective tissue nevi are benign hamartomatous lesions in which one or several of the components of the dermis (collagen, elastin, glicosaminoglycans) show predominance or depletion. Recently, de Feraudy et al broadened the spectrum of connective tissue nevus, describing fibroblastic connective tissue nevus (FCTN), which is characterized by proliferation of CD34+ cells of fibroblastic and myofibroblastic lineage. Only solitary papules and nodules have been described. We present the first case of FCTN with mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 16 publications
2
15
0
Order By: Relevance
“…In patient 1 there was an uncommon infiltration of the entire thickness of the subcutis with focal infiltration of the periosteum, which has never been reported. In patients 1 and 2, we report a superficial infiltration into the subcutis; this infiltration is also reported in 31 (67%) cases from the literature . In addition to CD34 positivity of the fibroblastic lineage, all other markers for spindle cells such as S100P, SMA, desmin, and myogenin were negative, except for a moderate focal SMA positivity in patient 3.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…In patient 1 there was an uncommon infiltration of the entire thickness of the subcutis with focal infiltration of the periosteum, which has never been reported. In patients 1 and 2, we report a superficial infiltration into the subcutis; this infiltration is also reported in 31 (67%) cases from the literature . In addition to CD34 positivity of the fibroblastic lineage, all other markers for spindle cells such as S100P, SMA, desmin, and myogenin were negative, except for a moderate focal SMA positivity in patient 3.…”
Section: Discussionsupporting
confidence: 72%
“…The overlying epidermis was normal histologically in all the cases we report, as opposed to the papillomatous epidermic pattern described in several cases . As in all cases reported (n = 46) in the literature, we did not find cellular atypias or mitoses; adnexal structures were entrapped but always spared . In patient 1 there was an uncommon infiltration of the entire thickness of the subcutis with focal infiltration of the periosteum, which has never been reported.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Bouaoud et al reported congenital FCTN in three infants with unusual features that were suggestive of sarcoma, lipoma, and vascular malformation. In 2016, Downey et al first reported a unique case of FCTN with multiple agminated lesions on the right lower leg of a 5‐month‐old boy, which was diagnosed as agminated FCTN. Although FCTN is typically a solitary lesion, agminated variants should be kept in mind.…”
Section: Discussionmentioning
confidence: 99%